THE DEVELOPMENT OF A RECEPTION SCHEDULE OF "САD3NIKOMED" AND "MGB6 FORTE" FOR COMPLEX TREATMENT OF CARIES RESISTANCE ON THEIR DAILY DYNAMICS - Evgeny Alexandrovich Melchenko; Kristina Richardasovna Urbashevichus (Современная наука и инновации)
In condition of high extension of dental caries in Russia it occurs the searching for means of increasing the resistance to caries. Despite the prevalence of modern filling materials and methods of sealing, the problem of treatment of caries is one of the leading places in restorative dentistry. Today there are a lot of of methotds of increasing the resistance to caries but not a single scheme of treatment is proposed, as each method has positive properties. But all the schemes that we found in the literaturecaptured neither daily dynamics of calcium nor its interaction with magnesium.